U.S. Court Ruling on Trump's Reciprocal Tariffs, the Role of the WTO, and Its Implications for the 19% Indonesia–U.S. Tariff Agreement - Amalia Dewi, Sari; Uwiyono, Aloysius; Saleh, Rosdiana (International Journal Labs, 2026)
The United States’ reciprocal tariff policy under President Donald Trump, implemented through the International Emergency Economic Powers Act (IEEPA), aimed to balance trade terms via unilateral tariff adjustments. However, the policy was declared illegal by several U.S. courts, including the Court of International Trade (CIT) and the Federal Circuit. At the same time, the World Trade Organization (WTO) has been effectively paralyzed due to the dysfunction of its Appellate Body, leaving no effective multilateral mechanism to address violations of the General Agreement on Tariffs and Trade (GATT). Amid this legal uncertainty, a 19 percent tariff agreement between Indonesia and the United States emerged in 2025 as a bilateral arrangement to stabilize trade relations. This study applies a legal-normative approach, focusing on the interpretation and analysis of legal norms derived from regulations, court decisions, and international agreements. By examining these elements through a doctrinal and positivist lens, the study evaluates the coherence and hierarchy of legal authority among U.S. domestic rulings, WTO obligations, and bilateral agreements. It argues that the intersection of U.S. rulings, WTO dysfunction, and bilateral agreements highlights fragmentation within the international trade law system. The traditional rules-based order championed by the GATT–WTO system has increasingly been supplanted by overlapping domestic laws and political compromises. The Indonesia–U.S. tariff agreement illustrates a shift from multilateral legal certainty to bilateral pragmatism, signaling the erosion of legal coherence and the growing dominance of executive discretion in modern trade governance.